2015
DOI: 10.1101/gad.254664.114
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinesis breaks dicentric chromosomes preferentially at pericentromeric regions and telomere fusions

Abstract: Dicentric chromosomes are unstable products of erroneous DNA repair events that can lead to further genome rearrangements and extended gene copy number variations. During mitosis, they form anaphase bridges, resulting in chromosome breakage by an unknown mechanism. In budding yeast, dicentrics generated by telomere fusion break at the fusion, a process that restores the parental karyotype and protects cells from rare accidental telomere fusion. Here, we observed that dicentrics lacking telomere fusion preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 76 publications
5
59
0
Order By: Relevance
“…This study used live-cell imaging to determine the fate of dicentric chromosomes formed during telomere crisis and showed that dicentric chromosomes do not break during mitosis. This finding was in agreement with work in yeast cells and a subsequent analysis in human cells 3,103,104 (FIG. 5a).…”
Section: Telomere Crisis and Genome Instabilitysupporting
confidence: 92%
“…This study used live-cell imaging to determine the fate of dicentric chromosomes formed during telomere crisis and showed that dicentric chromosomes do not break during mitosis. This finding was in agreement with work in yeast cells and a subsequent analysis in human cells 3,103,104 (FIG. 5a).…”
Section: Telomere Crisis and Genome Instabilitysupporting
confidence: 92%
“…Indeed, when ingression was blocked with the actomyosin inhibitor blebbistatin (Straight et al, 2003), the dicentric chromosomes clearly remained intact (0/24 events) (Figure 1F; MovieS1, panel 1). Thus, as is the case in budding yeast (Haber et al, 1984; Lopez et al, 2015; Hill and Bloom, 1989), mammalian dicentric chromosomes can withstand the forces of the mitotic spindle and do not break before cytokinesis. This result is not unexpected given that the spindle force (0.5-1.5 nN) is insufficient to break a mitotic chromosome, which can withstand at least 100 nN (Houchmandzadeh et al, 1997).…”
Section: Resultsmentioning
confidence: 84%
“…We suggest that nonrandom breakage of the dicentric chromosome, as has been seen in other organisms (Shimizu et al 2005;Pobiega and Marcand 2010;Song et al 2013;Lopez et al 2015), is the most likely explanation for the clustered locations of new telomeres. If breakage in euchromatin tends to occur at a few preferred sites, then viable twobreak combinations should be much more frequent than if breakage were random.…”
Section: Discussionmentioning
confidence: 92%